Thoughts on the Joanine Style in 18th-Century Luso-Brazilian Religious Decorations - Pedrosa, Aziz (Revista do Instituto Histórico e Geográfico Brasileiro, 2023)
The article aims to stimulate reflections on the gilded and polychrome woodwork of the Joanine Style found in 18th-century Luso-Brazilian churches and chapels. It begins with an overview of the cultural and artistic context fostered by the patronage of Dom João V (1689-1750), whose actions brought about changes in the Portuguese art scene, influencing Brazil. Through the analysis of these aspects, the article examines the influence of Portuguese art on Brazilian religious decoration between approximately 1720-1760. It highlights the presumed means used to enrich the formal repertoire of executed works, the formal characterization of remaining pieces, and the involvement of various artists involved in this process. Within this scope, the article also prompts reflections on the wooden ornamentation of the Joanine style in Brazil, a theme that is still insufficiently researched.